Formulation and Evaluation of Naproxen Tablets Produced using a Natural Binder - Eziuzo, Okafo Sinodukoo; Amarauche, Chukwu (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Sida acuta gum (SAG) is derived from the powdered dried leaves of the plant, Sida acuta burm. F (fam: Malvaceae).This study was conducted to evaluate naproxen tablets formulated using SAG as binder.SAG was isolated by maceration of the powdered dried leaves of Sida acuta and the subsequent precipitation of the formed mucilage with isopropyl alcohol. The precipitated gum was dried in an oven at 40 0C and stored in an airtight container. Tablets of naproxen were prepared by wet granulation method using 0.5, 1.0, 1.5, 2.0%of SAG (N1, N2, N3, N4 respectively), 1.5, 20% of acacia (N5,N6) and 1.5, 2.0% of sodium carboxymethylcellulose(N7, N8) as binders. Formulation N9 did not contain any binder. The tablets were evaluated for hardness, friability, disintegration time, in vitro dissolution and drug content. Tablet hardness ranged from 0.5 ± 0.00 (N9) to 4.00 ± 0.30 kgf (N3). Friability ranged from 0.13 (N7) to 2.19 % (N9). Disintegration time ranged from 0.17 ± 0.04 (N5) to 96 67 ± 5.77 min (N4). The percentage drug released after 45 min, from all the formulations was 100 % except for N3 (21.59 %), N4 (20.20 %), N7 (23.04 %) and N8 (19.57 %). Naproxen tablets were successfully formulated using SAG as binder.Tablet disintegration time increased with increased binder concentration for all the formulations.